Measurement of the aversion towards risk through the use of the game "Ber nebo neber" - Krkošková, Magdalena; Potužák, Pavel; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
I explore the decision-making process of the contestats of the TV game show "Deal or no deal" in Czech version "Ber nebo neber". This decision-making process does not require any further skills or knowledge and it is based on the large stakes and deal or no deal decisions by accepting or rejecting possibility of continuing in the game. Based on the panel data set gathered from real played games, it is possible to determine the risk averse or risk seeking attitude of the contestants. The data set contains 28 episodes, 23 obtained directly from TV Prima and 5 of them from private sources, both between years 2007 and 2008. I assume the contestants under myopic and hyperopic framing and I find the average Arrow-Pratt coefficient of relative risk aversion (RRA). I consider different wealth levels and generally the RRA is lower for hyperopic framing. The differences in RRA may be most explained by the prior losses variable, which pictures the previous duration of the contestant's game.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses